Distribuição de tensões em restaurações anteriores e posteriores com diferentes materiais e linhas de cimento: análise tridimensional por elementos finitos - Kintopp, Cibele de Almeida (2021)
The objective of this thesis was to evaluate, using three-dimensional finite element analyzes and micro-CT data obtained through realistic models, the stress distribution in the restoration and in the resin cement layer: 1) of different prosthetic preparations; and 2) indirect posterior partial restorations made of different materials (composite resin, lithium disilicate-based glass-ceramic, polymer-infiltrated ceramic and zirconia). Four replicas of a healthy maxillary central incisor and a healthy mandibular first molar were obtained. Different preparations were performed, with four preparations for the anterior ones (butt joint (BJ), palatal chamfer (CP), palatal chamfer, involving oblique fracture of the distal angle (FO-CP), and palatal chamfer involving incisal fracture (FI-CP) and four preparations for posterior (inlay, onlay, endocrown and occlusal veneer) Indirect restorations were made of composite resin from an acetate matrix and cemented on the replicas with resin cement. The specimens were microtomographed and three-dimensional finite element models were In the previous preparations, an evenly distributed load of 100 N was applied to the palatal surface, 2 mm below the incisal edge at angles of 60° and 125° in relation to the longitudinal axis. cement lines and tooth structure were calculated and analyzed.BJ preparation showed better stress distribution than CP preparation FI-CP preparation showed better voltage distribution than FO-CP. Ceramic veneers had lower stresses than composite resin veneers. It was concluded that the different prosthetic preparations for laminated veneers influenced the stress distribution in the restoration and in the resin cement layer for resin and ceramic. In the subsequent preparations, a load of 500 N was applied, simulating three points of occlusion. The endocrown had lower tensions, while the inlays had greater magnitude tensions. In relation to the restorative materials, zirconia and glass-ceramic presented higher tensions in the restorations, followed by ceramic infiltrated by polymer and composite resin. This difference between restorative materials was greater in inlays and endocrowns than in onlays and occlusal veneers. The cusp coating in the onlay preparation, in comparison with the intracoronary inlay preparation, presented lower tensions and more favorably distributed. It can be concluded that the different prosthetic preparations for partial posterior single restorations influenced the stress distribution in the restoration, in the resin cement line and in the remaining tooth structure.